Arbuscular mycorrhizal status of indigenous tree species used to restore seasonally dry tropical forest in northern Thailand - Nandakwang P. (2014)
Arbuscular Mycorrhizal (AM) status of native plants in the tropical forest of northern Thailand was surveyed. Twenty four framework tree species, used to forest restoration were examined at 3 sites: FORRU's research tree Nursery (FN), Forest Restoration plot (FR) and Natural Forest (NF). Eleven dominant herb species were examined at 2 sites: Degraded Watershed (DW) and Forest Soil extraction area (FS). Rhizosphere soil samples were collected and AM fungal spores were counted and identified morphologically. Most plant species were intensively colonized by AM fungi except Cyperus cyperoides. Twenty four AM species were identified: Glomus (15 species), Acaulospora (6 species) and Scutellospora (3 species). Glomus rubiforme was the dominant species. Spore density varied from 16.1 to 97.4 per 100 g soil (averaged 59.7). Spore number at DW and FS were 129 and 479 spores, respectively, with species richness of 6 and 8, respectively. Spore number at FN, FR and NF were 1,152, 2,337 and 1,376 spores, respectively, with species richness of 17, 21 and 15, respectively. The AM diversity was lower in the sites dominated by herbs than in sites examined for trees. In the deforested sites, reduced plant diversity was related with reduced mycorrhizal diversity. In contrast, the trial plot had the highest AM fungal community. Therefore, the forest restoration techniques allow tree species grown in nursery to become AM associated. The association is still maintained after planting out trees in restored area. © 2008 Academic Journals Inc.